Pemberhentian Presiden Dan/Atau Wakil Presiden Dalam Undang-Undang Dasar Negara Republik Indonesia 1945 Pasca Perubahan - Ucha Widya (Universitas Islam Indonesia, 2022)
After the amendment to the 1945 Constitution, the president was no longer subject to and responsible to the MPR. The President cannot be dismissed by the People’s Consultative Assembly (MPR) during his term of office by reason of a vote of no confidence or political reasons. The president can only be dismissed through the process of impeachment as regulated in Article 7A and Article 7B of the 1945 Constitution of the Republic of Indonesia. This study examines 2 (two) issues, first, how is the mechanism for dismissing the president and/or vice president in the 1945 Constitution of the Republic of Indonesia after the amendment? Second, why is the dismissal of the president and/or vice president through the impeachment process referred to as a political decision? This research is normative, the approach taken includes a statutory approach. The results of the study conclude that first, the mechanism for dismissing the president and/or vice president after the amendment involves 3 institutions, namely the MPR, House of Representatives (DPR) and Constitutional Court (MK) with the basic reason of being a disgraceful act that is contrary to the principle of legality and the principle of legal certainty. Second, absolute authority in impeachment cases is the constitutional right of the MPR, because the Constitutional Court is only given the obligation of legal opinion to the DPR, this is a step by the state of law to decide political cases with valid evidence. The dismissal of the president and/or vice president through the impeachment process still dominates, considering that after the Constitutional Court decided the impeachment case was brought to the MPR, and the MPR consisted of the DPR.Key Words: Dismissal of the president and/or vice president; post-amendmentAbstrakSetelah amandemen UUD 1945, presiden tidak lagi tunduk dan bertanggung jawab kepada MPR. Presiden tidak dapat diberhentikan oleh MPR selama masa jabatannya dengan alasan mosi tidak percaya atau alasan politik. Presiden hanya dapat diberhentikan dengan melalui proses pemakzulan sebagaimana diatur dalam Pasal 7A dan Pasal 7B UUD NRI 1945. Penelitian ini mengkaji 2 (dua) hal, pertama, bagaimana mekanisme pemberhentian presiden dan/atau wapres dalam UUD NRI 1945 pasca perubahan? Kedua, mengapa pemberhentian presiden dan/atau wapres melalui proses impeachment disebut sebagai keputusan politik? Penelitian ini bersifat normatif, pendekatan yang dilakukan meliputi pendekatan perundang-undangan. Hasil kajian menyimpulkan bahwa pertama, mekanisme pemberhentian presiden dan/atau wakil presiden pasca amandemen melibatkan 3 lembaga yaitu MPR, DPR dan MK dengan alasan mendasar karena perbuatan tercela yang bertentangan dengan asas legalitas dan asas kepastian hukum. Kedua, kewenangan mutlak dalam perkara pemakzulan adalah hak konstitusional MPR, karena MK hanya diberikan kewajiban pendapat hukum untuk DPR, ini merupakan langkah negara hukum yang memutus perkara politik dengan alat bukti yang sah. Pemberhentian presiden dan/atau wapres melalui proses impeachment masih mendominasi, mengingat setelah Mahkamah Konstitusi memutuskan kasus impeachment dibawa ke MPR, dan MPR terdiri dari DPR.Kata-kata Kunci: Pemberhentian presiden dan/atau wakil presiden; pasca perubahan